Antioxidant Vitamins and Their Use in Preventing Cardiovascular Disease - Farbstein, Dan (MDPI, 2010)
Atherosclerosis remains one of the leading causes of death in Western populations. Subsequent to the discovery that oxidative stress plays a pivotal role in the development and progression of atherosclerosis, vitamins C and E, along with other antioxidants, were studied as potential therapies for the disease. However, while in vitro and in vivo studies showed promising antiatherogenic effects for vitamins C and E, clinical trials in which patients were given high doses of vitamin E or C showed no benefit and even possible harm. This review will attempt to summarize the known mechanistic data regarding the biochemical effects of vitamins C and E and their relevance to atherosclerosis, and offer an explanation for the failure of clinical trials to show that supplementation with these vitamins provides any benefit when given indiscriminately. We provide one example of how pharmacogenomics may be used to identify a sub-population which may indeed benefit from antioxidant supplementation.